2015
DOI: 10.1172/jci78089
|View full text |Cite
|
Sign up to set email alerts
|

T cells in the control of organ-specific autoimmunity

Abstract: R e v i e w S e R i e S : A u t o i m m u n i t y2 2 5 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 202 publications
2
94
0
1
Order By: Relevance
“…We evaluated T-cell receptor (TCR) b-chain diversity prior to and after expansion, and found that polyclonality was maintained, without preferential expansion of a limited cell clonotypes, suggesting the expansion of a highly diverse Treg cell population. We noted that the expanded Tregs up-regulated several functional cell surface markers, including CCR7, CD38, CD25, CTLA-4, and LAP, which suggested enhanced activity of the expanded cells [16,17].…”
Section: Treg Manufacture For Clinical Usementioning
confidence: 85%
See 1 more Smart Citation
“…We evaluated T-cell receptor (TCR) b-chain diversity prior to and after expansion, and found that polyclonality was maintained, without preferential expansion of a limited cell clonotypes, suggesting the expansion of a highly diverse Treg cell population. We noted that the expanded Tregs up-regulated several functional cell surface markers, including CCR7, CD38, CD25, CTLA-4, and LAP, which suggested enhanced activity of the expanded cells [16,17].…”
Section: Treg Manufacture For Clinical Usementioning
confidence: 85%
“…To control autoimmunity, a number of suppressor cell populations have been defined in rodents and man, including regulatory B cells, dendritic cells and macrophages. However, regulatory T cells (Tregs) have emerged as the major cell subset maintaining tolerance, with the ability to potently suppress the activation and effector function of other immune cells, including CD4 and CD8 T cells, B cells, NK cells, macrophages, and dendritic cells [15,16]. Tregs encompass various subsets of CD4 þ and CD8 þ cells and may develop centrally in the thymus (tTregs) or in the periphery from conventional T cells (pTregs) in response to activation signals and exposure to cytokines such as TGFb and retinoic acid (Fig.…”
Section: Treg Overview and Role In Dmmentioning
confidence: 99%
“…Although Treg-based therapies hold great promise for treatment of autoimmunity, it is unclear whether a general expansion of the Treg population in patients with autoimmunity is an efficient or effective approach. It is more likely that therapies focused on tissue antigen-specific Tregs would be more efficacious, as the cells could home to the appropriate tissue site and exert local, robust suppression (42,43). Unfortunately, isolation of sufficient numbers of human antigen-specific Tregs is a challenging prospect; therefore, the use of alternative markers associated with functional self-reactive Tregs should be explored.…”
Section: Among the 1328 Genetic Transcripts Increased In Cd5mentioning
confidence: 99%
“…Jeffrey Bluestone and colleagues discuss how CD4 + Tregs control the outgrowth of potentially pathogenic self-reactive cells (10). In…”
Section: Discussionmentioning
confidence: 99%